LEFT GLOBAL DIMENSIONS AND INVERSE POLYNOMIAL MODULES - Park, Sangwon (International Journal of Mathematics and Mathematical Sciences, 2000)
We prove the fact l. gl. dimR[x] = (l. gl. dimR)+1, where l.gl.dim means the left global dimension by using inverse polynomial modules and injective dimensions. The classical way to prove the fact l. gl. dimR[x] = (l. gl. dimR)+1 is using polynomial modules and projective dimensions.